Relationship between Using Masks and Incidence of Acute Respiratory Infection in Marble Stone Workers - Yuliastuti, Wiwid; Suharyoto, Suharyoto; Suciati, Suciati; Indrawati, Leny; Islamy, Aesthetica (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The use of personal protective equipment masks is an important factor in protecting workers from potential hazards while working in marble processing. Many diseases are caused by exposure to dust, especially acute respiratory infections (ARI). The purpose of this study was to determine the relationship between the use of masks and the incidence of ARI in marble stone workers in Besole village, Besuki Tulungagung district. The design of this study is an analytic association using a cross-sectional design. The population is all marble stone workers in Besole village, Besuki Tulungagung district. The sample size is 44 respondents, the sampling technique uses purposive sampling. The independent variable of this study is the use of masks and the dependent variable is the incidence of ARI. Data collection using a questionnaire was given to marble workers in Besole Village, Besuki Tulungagung sub-district. Data analysis used the Spearman Rho statistical test with Confidence Interval (CI): of 95% or ï¡ = 0.05. The results showed that most of the respondents, 28 respondents (64%), wore masks and half of the respondents, 22 respondents (50%), had mild ARI. The statistical test results showed p value = 0.015 < Î± = 0.05 which means H0 was rejected so it can be stated that there is a relationship between the use of masks and the incidence of ARI in marble stone workers. The conclusion from the results of this study is the use of masks when working properly and correctly as self-protection from dust so that marble workers do not experience pain, especially ARI.